2012
DOI: 10.1186/1471-2393-12-16
|View full text |Cite
|
Sign up to set email alerts
|

Timing of antenatal care for adolescent and adult pregnant women in south-eastern Tanzania

Abstract: BackgroundEarly and frequent antenatal care attendance during pregnancy is important to identify and mitigate risk factors in pregnancy and to encourage women to have a skilled attendant at childbirth. However, many pregnant women in sub-Saharan Africa start antenatal care attendance late, particularly adolescent pregnant women. Therefore they do not fully benefit from its preventive and curative services. This study assesses the timing of adult and adolescent pregnant women's first antenatal care visit and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

52
232
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(290 citation statements)
references
References 44 publications
52
232
5
1
Order By: Relevance
“…27 However, a previous study conducted in Myanmar reported much lower gestational age at first ANC (15 weeks) while those detected in Ethiopian and Tanzanian studies were more than 20 weeks. 14,18,24 These discrepancies may be due to differences in time or site of study or differences in education and/or socioeconomic status among study population. Difference in culture or level of awareness on the significance of early initiation of ANC could explain these variations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 However, a previous study conducted in Myanmar reported much lower gestational age at first ANC (15 weeks) while those detected in Ethiopian and Tanzanian studies were more than 20 weeks. 14,18,24 These discrepancies may be due to differences in time or site of study or differences in education and/or socioeconomic status among study population. Difference in culture or level of awareness on the significance of early initiation of ANC could explain these variations.…”
Section: Discussionmentioning
confidence: 99%
“…14,19 However, studies conducted in developed countries revealed lower proportions (4.4% to 27.3% % in USA, about 15% in UK and 41% in Australia) whereas some African studies reported comparable or higher values (53% in Ethiopia, 61.1% in Rwanda, 70.3% in Zambia, 81% in Nigeria, more than 70% in Tanzania and Malawi). 5,[16][17][18][20][21][22][23][24][25] Utilization of different cut-off points in defining late initiation of ANC could explain these discrepancies (first trimester or 12 completed weeks was used in USA and UK studies, 16 weeks in Ethiopian, Zambian, Tanzanian and Malawi studies, and second/third trimester in some studies). 5,[16][17][18][19][20]22,24,25 The proportions of pregnant women who initiate ANC before 4 months of gestation among neighboring and ASEAN countries were 40.4% in Bangladesh, 32.2% in Cambodia, 56.9% in India, 78.6% in Indonesia, 37.5% in Nepal, 46.9% in Pakistan, 56.1% in the Philippines and 65% in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports from throughout sub-Saharan Africa have recognized some of these barriers, but a number of these studies have been quantitative surveys. It is interesting to note that when a structured questionnaire 4,11,12,14,15 is used there is more emphasis on the practical barriers to attendance whereas the more open-ended, lessconstrained approach with a qualitative study 5,[6][7][8]10 enables the identification of additional and more complex barriers. During the first three months the barriers are almost entirely identified by qualitative studies.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout sub-Saharan Africa, in addition to social taboos, there is evidence that women are unsure of the purpose behind antenatal care 7 , probably due to a belief that childbearing represents a normal ‗bodily experience' rather than an illness 8 . Practical barriers to using antenatal care include remoteness from treatment facilities and costs [9][10][11] , a belief that attendance is necessary to obtain a document that permits delivery within the hospital 8 , and the attitude of health professionals [12][13][14][15] . The barriers to antenatal care remain unstudied in an urban context.…”
Section: Introductionmentioning
confidence: 99%